Impact of Insecticide Cartap Hydrochloride on Bacterial Biofertilizers - Kaur, Loveleen (My University, 2017)
Soil microorganisms play an important role in maintaining ecological balance through active participation in carbon, nitrogen, sulphur and phosphorous cycles. Agricultural microbials such as Pseudomonas striata and Azotobacter sp., used as biofertilizers, play a significant role in plant nutrition by increasing phosphate uptake and nitrogen fixation respectively. Indiscriminate use of insecticides to control crop losses from insect pests has increased considerably. Cartap hydrochloride is one of the widely applied insecticide to control a wide range of sucking and chewing insect pests of paddy crop and vegetables. Present study reports the uptake of cartap hydrochloride by bacterial inoculants (Pseudomonas striata and Azotobacter CBD15) using enrichment technique. Bacterial biofertilizers were grown in minimal medium containing different concentration of cartap hydrochloride (0-100 ppm). There was a stimulatory effect on the growth of both the strains, which indicates that bacteria were utilizing insecticide as carbon and nitrogen source. LD50 was 50 ppm for Azotobacter CBD15 and 90 ppm for Pseudomonas striata. Effect of cartap hydrochloride on growth, IAA production and phosphate solubilisation by these bacterial inoculants was carried out along with determination of its residual concentration. 50 ppm cartap hydrochloride had stimulatory effect on phosphate solubilisation by Azotobacter CBD15 (42.8%) and Pseudomonas striata (52.9%) as compared to control. 6.5mg/ml of IAA was produced by Pseudomonas striata at 100 ppm and 3.3mg/ml of IAA was produced by Azotobacter CBD15 at 50 ppm of cartap hydrochloride. The study revealed that cartap hydrochloride can be safely used with no deleterious effect on the growth and desirable biochemical activity of bacterial biofertilizers at its recommended dose (10 ppm) of field application.
Master of Science -Biotechnology
Keywords: Insecticide; biofertilizers; Azotobacter; Pseudomonas